Gereja yang Mendengar: Respons Pastoral terhadap Penderitaan yang Disebabkan oleh Emosi Malu - Lamria Sinaga (Indonesian Journal of Theology, 2022)
Emotions of shame, guilt, and fear reflect ubiquitous if not normalized aspects of the human experience. This article seeks to explore how the church makes use of the emotion of shame in its theologizing. While shame is an oft discussed topic in psychology and counseling therapy, religious traditions have the tendency to exacerbate such an emotion—which can be seen in how the so-called ideals of the church can alienate those struggling with shame, even to the point of “disappearing” those who suffer. It stands to reason that in this alienating the church lacks a sufficient understanding of shame to proffer it of any use for its theologizing. Following a literature survey of qualitative research methods, this article employs a constructive theological method that considers how relevant a proper comprehension of emotions like shame prove to be for pastoral theology. This article concludes that the emotion of shame, rather than presenting an abyss between humanity and God, is a space to meet the God of perfection, namely, within the vulnerability and suffering of human persons, by means of a listening church.